Development of Islamic Entrepreneurial Spirit Among UINSU Students by Utilizing Digital Technology - Azmi, Syahfrilla Al Risa Nurul; Nawawi, Zuhrinal M. (AMK : Abdi Masyarakat UIKA, 2024)
Developing an Islamic entrepreneurial spirit among UINSU students is an important step in creating a generation that is creative, competitive, and based on Islamic principles. The use of digital technology in developing an Islamic entrepreneurial spirit among UINSU students offers various opportunities and challenges. Digital technology is an effective means of building an entrepreneurial ecosystem that is inclusive, innovative, and oriented towards Islamic values. This research uses literacy methods. The use of this method is a person’s ability to process and understand information when carrying out the reading and writing process. Thus, entrepreneurship can grow within a framework that is in accordance with Islamic teachings. In addition, the use of digital technology such as e-commerce platforms and Sharia financial applications can provide easier access for Islamic business actors to participate in the global economy. This not only expands market reach but also increases competitiveness sustainably. Another aspect that is no less important is Islamic entrepreneurship education through digital platforms.